Cover Image, Volume 53, Issue 2. Issue 2 (8th April 2020) - Unknown
Abstract : Cover : Cover crops have many positive benefits, but on the negative side of the ledger, they can be attractive environments for pests to lay eggs or overwinter. An article on p. 3 of this issue provides some general tips to reduce pest problems as well as advice specific to controlling stink bugs, slugs, and bean leaf beetles. Cover photo shows wireworms feeding on a corn root. Cover crops can aggravate wireworm damage in corn by providing a year‐round food source. Source: Scott Stewart, The University of Tennessee.